HUBUNGAN MUTU PELAYANAN ASUHAN KEPERAWATAN DENGAN PASIEN PULANG PAKSA DI PUSKESMAS RAMBIPUJI KABUPATEN JEMBER - Said Mardjanto; Sujud Priono (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2017)
The quality of nursing services as an indicator of the quality of health services is one of the determining factors in the image of health care institutions in the eyes of the community. This happens because nursing is the professional group with the highest number, front and closest to the suffering, pain, and suffering experienced by patients and families. . The research design used is the Cross Sectional approach. The study population was class II inpatients, as many as 40 respondents. The sampling technique used accidental sampling using observation sheet and questionnaire instruments. The results showed that the quality of nursing care services was not carried out completely as much as 70%, and the incidence of forced discharge as much as 60%. The results of data analysis with Chi Square at α = 0.05 obtained p value = 0.003, then ho was rejected and ha was accepted, which means there is a relationship between the quality of nursing care services with patients being forced to go home at the Pusipuji Health Center in Jember Regency. It is recommended to health services to pay more attention to the quality of nursing services, especially how to document nursing care properly and completely